TINJAUAN ATAS PROSEDUR PEMBAYARAN BMN BERUPA ASET TETAP KENDARAAN PADA BADIKLAT PKN BPK RI - Astrid Andini (2021)
This final project report aims to learn about the payment of state property procedure in the word of work of work and has a specific purpose in writing this final project, namely as requirement for graduation from the Diploma Three (III) program for the accounting Pembangunan Nasional Veteran Jakarta university. In crrying out the field work practice, there are many adventages that can be taken as a student, one of which is that student can apply the knowlage that has been given by the lecturer ehile studying in the word of work. The author chose the place of filed vork practice at BADIKLAT PKN BPK RI located on Jl. BPK RI Taining Center Jl. Raya Kalibata RT.6/RW.7, Kalibata south jakarta, DKI Jakarta. Special capital region of jakarta. BADIKLAT PKN BPK RI is company in the field of education service. While crrying out of the field work practice, the author was placed in the General an IT sub-section. The procedure is a flow that must be obeyed by each sub-section for the sake of good cooperatition and achieving the goals of a company. Payment of state property procedures in the form of Fixed Assets Vehicles are needed to meet the need and launch the company's operations. In addition, in purvhasing the vehicle's fixed assets, there is a procecc of purchasing goods and services through the e-catalogue application by using the applivation, thestate property payment process in the form of fixed assets of vehicles and other assets futher invreases the efficiency, effectivieness, transparancy, and accountability of the company. After crrying out the field work practice, it can be concluded that it can make students more ready to seek experienve in the world of work. So that later it becomes a provision for writers to enter the world of work.